ASTOVL Combat Aircraft Design Synthesis and Optimization - Kehayas, N. (Cranfield University, 1992)
This thesis presents the development of a Baseline Configuration for an Advanced Short Take-Off and Vertical Landing (ASTOVL) Combat Aircraft, the Design Synthesis and coding of this Baseline Congiguration (Code VERTI), the interfacing of the Design Synthesis Code VERTI with the Optimizer code RQPMIN and the optimization of the Baseline Configuration. The background and the objectives of this Research Programme are initially examined. The evaluation of the ASTOVL Combat Aircraft Baseline Configuration is then described, including all the problems, assumptions, choices and compromises that led to the specific configuration. The development of the Design Synthesis and the Code VERTI then follow, where the methodology used, the techniques adopted and the code operation are explained. A full description of the Design Synthesis is included as an appendix. Finally, the interfacing of Code VERTI with the optimizer RQPMIN and the optimization of the Baseline configuration are presented. The problems and difficulties of the RQPMIN operation are thoroughly discussed. The RQPMIN- VERTI code is used to optimize the initial Baseline Configuration and an optimization example is provided in appendix form. The optimized Baseline Configuration is partly validated against two ASTOVL combat aircraft designs. In addition to the optimization with the aircraft empty mass as objective function, a search for a better objective function is attempted.